Studies on the potential of Borana cattle - Obradovic, O.; Haile, Aynalem (1975)
Presents data on live weight and its variation with the seasons, conception rate, gestation length, calving rate, lactation length and milk yield of Boran cows.Discussions and data on birth weight, live weight change, feed and water consumption of their calves and comparisons of carcass values of Borana cattle fattened on different feeding regimes included.